Patient Preferences for Discussing and Acting on Health-Related Needs in Primary Care. (August 2022) - O'Loughlin, Kristen; Shadowen, Hannah M.; Haley, Amber D.; Gilbert, Jennifer; Lail Kashiri, Paulette; Webel, Ben; Huebschmann, Amy G.; Krist, Alex H.
Background: Addressing social needs, health behaviors, and mental health may help patients more than traditional medical care. However, these root causes of poor health are difficult to address and the role of primary care is unclear. This qualitative study assesses patient's willingness and motivations to discuss and accept assistance for these needs from their primary care team. Methods: In July and August of 2020, semi-structured virtual interviews were conducted with family medicine patients (n = 6) and residents of low resource neighborhoods (n = 11) in Richmond, Virginia. Interviews were conducted over Zoom. We conducted a qualitative analysis of patient and resident interview transcripts. A rapid qualitative analysis approach and immersion-crystallization processes were used to identify themes and categories. Results: Interviewees reported varying degrees of comfort discussing topics with their health care team. They were less comfortable discussing needs they considered outside the realm of "traditional primary care" including finances, transportation, and housing, but interviewees expressed willingness to discuss these needs under certain conditions. Important factors were a strong patient-clinician relationship to create a trusted and safe space for discussion, adequate time for discussion during visits, communication of practices' ability to provide resources to help patients, and ensuring appropriate high quality referrals. Conclusions: Primary care provides opportunity for identifying and addressing needs that adversely impact health. Some needs are more sensitive for patients to work with their care team on, though, there was willingness to work on any need when a strong provider relationship and clinic structure for providing support were in place. This study highlights critical care delivery factors which may be used to enhance patient comfort accepting support for their needs and ultimately improve clinical care and chronic disease management.